Isocitrate dehydrogenase 1–mutated human gliomas depend on lactate and glutamate to alleviate metabolic stress. Issue 1 (12th July 2018) - Lenting, Krissie; Khurshed, Mohammed; Peeters, Tom H.; van den Heuvel, Corina N. A. M.; van Lith, Sanne A. M.; de Bitter, Tessa; Hendriks, Wiljan; Span, Paul N.; Molenaar, Remco J.; Botman, Dennis; Verrijp, Kiek; Heerschap, Arend; et al.
ABSTRACT: Diffuse gliomas often carry point mutations in isocitrate dehydrogenase ( IDH1 mut ), resulting in metabolic stress. Although IDH mut gliomas are difficult to culture in vitro, they thrive in the brain via diffuse infiltration, suggesting brain‐specific tumor–stroma interactions that can compensate for IDH‐1 deficits. To elucidate the metabolic adjustments in clinical IDH mut gliomas that contribute to their malignancy, we applied a recently developed method of targeted quantitative RNA next‐generation sequencing to 66 clinical gliomas and relevant orthotopic glioma xenografts, with and without the endogenous IDH‐1 R132H mutation. Datasets were analyzed in R using Manhattan plots to calculate distance between expression profiles, Ward's method to perform unsupervised agglomerative clustering, and the Mann Whitney U test and Fisher's exact tests for supervised group analyses. The significance of transcriptome data was investigated by protein analysis, in situ enzymatic activity mapping, and in vivo magnetic resonance spectroscopy of orthotopic IDH1 mut ‐ and IDH wt ‐glioma xenografts. Gene set enrichment analyses of clinical IDH1 mut gliomas strongly suggest a role for catabolism of lactate and the neurotransmitter glutamate, whereas, in IDH wt gliomas, processing of glucose and glutamine are the predominant metabolic pathways. Further evidence of the differential metabolic activity in these cancers comes from in situ enzymatic mapping studies and preclinical in vivo magnetic resonance spectroscopy imaging. Our data support an evolutionary model in which IDH mut glioma cells exist in symbiosis with supportive neuronal cells and astrocytes as suppliers of glutamate and lactate, possibly explaining the diffuse nature of these cancers. The dependency on glutamate and lactate opens the way for novel approaches in the treatment of IDH mut gliomas.—Lenting, K., Khurshed, M., Peeters, T. H., van den Heuvel, C. N. A. M., van Lith, S. A. M., de Bitter, T., Hendriks, W., Span, P. N., Molenaar, R. J., Botman, D., Verrijp, K., Heerschap, A., ter Laan, M., Kusters, B., van Ewijk, A., Huynen, M. A., van Noorden, C. J. F., Leenders, W. P. J. Isocitrate dehydrogenase 1–mutated human gliomas depend on lactate and glutamate to alleviate metabolic stress. FASEB J. 33, 557–571 (2019). www.fasebj.org